2016
DOI: 10.1051/0004-6361/201527638
|View full text |Cite
|
Sign up to set email alerts
|

Strong-lensing analysis of MACS J0717.5+3745 fromHubbleFrontier Fields observations: How well can the mass distribution be constrained?

Abstract: We present a strong-lensing analysis of MACSJ0717.5+3745 (hereafter MACS J0717), based on the full depth of the Hubble Frontier Field (HFF) observations, which brings the number of multiply imaged systems to 61, ten of which have been spectroscopically confirmed. The total number of images comprised in these systems rises to 165, compared to 48 images in 16 systems before the HFF observations. Our analysis uses a parametric mass reconstruction technique, as implemented in the L software, and the subset … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 57 publications
9
124
0
Order By: Relevance
“…This could imply that the dark matter and galaxies are already past pericenter and in the "return phase" of the merger (Ng et al 2015). Interestingly, the dark matter peak is located even further to the east (as reported by e.g., Johnson et al 2014;Limousin et al 2016), although other lensing models show better agreement between the BGC location and mass surface density (e.g., Ishigaki et al 2015). From a core size of about 0 4 (≈150 kpc) and a temperature of 6.8 keV, we compute a sound crossing time of1 10 8 year for the core.…”
Section: Merger Scenariomentioning
confidence: 54%
See 2 more Smart Citations
“…This could imply that the dark matter and galaxies are already past pericenter and in the "return phase" of the merger (Ng et al 2015). Interestingly, the dark matter peak is located even further to the east (as reported by e.g., Johnson et al 2014;Limousin et al 2016), although other lensing models show better agreement between the BGC location and mass surface density (e.g., Ishigaki et al 2015). From a core size of about 0 4 (≈150 kpc) and a temperature of 6.8 keV, we compute a sound crossing time of1 10 8 year for the core.…”
Section: Merger Scenariomentioning
confidence: 54%
“…This structure seems to be associated with mass componentA, and is also seen in the mass surface density map from Ishigaki et al (2015). However, Johnson et al (2014) and Limousin et al (2016) place the center of the westernmost mass component about 0 5east of the center of the X-ray component. We discuss this "fly-through" bullet-like core in more detail in Section 4.3.…”
Section: Global X-ray Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…Remarkably, this study has revealed an exceptional number of central multiple images, which, within the inner 20 kpc, is approximately a factor of 4 larger than in any other known cluster to date. As a result, this spectroscopic data set has allowed us to obtain a very robust estimate of the inner slope of the projected total mass density profile and a detailed reconstruction of the inner projected mass distribution, which has been shown to be challenging when using photometrically selected multiple images (Limousin et al 2016). We summarize our results as follows:…”
Section: Discussionmentioning
confidence: 83%
“…those for which such features have been spectroscopically confirmed. Magnification estimates were derived by means of Lenstool (Jullo & Kneib 2009) from the positions of strong-lensing features and a parametric model which includes the contribution from clusterscale and galaxy-scale haloes (following the same approach as, e.g., Richard et al 2010;Limousin et al 2015). The available models allowed us to calculate the magnification due to cluster gravity for the ten high-redshift candidates presented in Table 3.…”
Section: Magnificationmentioning
confidence: 99%